Barriers to community engagement during the response to an Ebola virus disease outbreak in Uganda - Ann Robins; David Musoke; Henry Mwebesa; Edwinah Atusingwize; George Upenytho; Seungwoo Nam; Jesse Bonwitt; Chimwemwe Msukwa; Meddy Rutayisire; Henry Kyobe (BMJ Global Health)
Background Uganda reported an outbreak of Ebola virus disease (EVD) in 2022. As part of the outbreak response, government and partners promoted community engagement, which seeks to involve communities in the design, implementation and evaluation of interventions to raise awareness, build trust between communities and partners and create ownership of interventions. This study, therefore, explored barriers to community engagement during the 2022-2023 EVD outbreak response in Uganda.Methods This qualitative study, conducted in five districts (Kampala, Kassanda, Kyegegwa, Mubende and Wakiso), involved 25 focus group discussions among community members and community health workers (CHWs). In addition, 32 key informant interviews were conducted with staff from the Uganda Ministry of Health, district health officials, local leaders, non-governmental organisation staff and other stakeholders. Data were analysed according to the thematic approach using ATLAS.ti (V.6).Results The main barriers to community engagement identified during the EVD outbreak response are presented under four main themes: (1) delayed consultations between partners and communities; (2) poor communication and misinformation; (3) limited support to human resources; and (4) institutional and coordination challenges. Specifically, these barriers included: limited consultation due to misbelief in community roles; delayed sociocultural discussions; stigma and delayed psychosocial interventions; misinformation, rumours and political influence; poor communication mechanisms; contradictory messages and lack of transparency; language barrier and inappropriate communication media; work overload for CHWs and other community volunteers; failure to prioritise protection of community workers; lack of compensation for CHWs and other community personnel; poor logistical management; inadequate coordination and partner operations; unfavourable institutional structures; and limited funding for emergencies.Conclusion The barriers encountered in community engagement during the 2022-2023 EVD outbreak need to be addressed through strengthening guidelines and standard operating procedures, capacity building for partners and communities, as well as adequate financing to ensure Uganda is better prepared for future health emergencies.